Study on the Current Performance of Piping and Structure Coatings in Oil and Gas Field - Mohd Ridzuan bin Abdul Rahim, Mohd Ridzuan (Universiti Teknologi Petronas, 2009)
The objective of this project is to investigate the performance of the current piping and structure coatings (outer surface) in oil and gas field. The experimental works including metallography, scanning electron microscopy (SEM), cathodic disbondment test, and pull-off adhesion test described the real performance of the coatings.